1997
DOI: 10.1111/j.1600-0897.1997.tb00316.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Antibodies Generated Against a Conserved Portion of Oviductal Glycoprotein (OGP) and Endogenous Hamster OGP and Their Ability to Decrease Sperm Binding to the Zona Pellucida In Vitro

Abstract: These results suggest that OGP may be a potential immunocontraceptive target because both antibodies significantly decreased sperm binding to the ZP of oviductal oocytes. Immunocontraception may be accomplished by attempting to generate active immunity to a recombinant OGP, to the region selected in this study (amino acids 52-68) or to some other region of the core protein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
2

Year Published

2000
2000
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 36 publications
0
11
2
Order By: Relevance
“…Because pOSP was incubated with oocytes and sperm, modifications of zona pellucida receptors by co-operative action between pOSP and corticol granule contents may have occurred, as may alterations to the spermatozoa membrane. Results from this study appear to contradict findings observed in the hamster [49,50] and in humans [51]. Those studies [49][50][51] found an increased number of spermatozoa bound to the oocyte when exposed to OSP.…”
Section: Discussioncontrasting
confidence: 82%
See 2 more Smart Citations
“…Because pOSP was incubated with oocytes and sperm, modifications of zona pellucida receptors by co-operative action between pOSP and corticol granule contents may have occurred, as may alterations to the spermatozoa membrane. Results from this study appear to contradict findings observed in the hamster [49,50] and in humans [51]. Those studies [49][50][51] found an increased number of spermatozoa bound to the oocyte when exposed to OSP.…”
Section: Discussioncontrasting
confidence: 82%
“…Results from this study appear to contradict findings observed in the hamster [49,50] and in humans [51]. Those studies [49][50][51] found an increased number of spermatozoa bound to the oocyte when exposed to OSP. The differences between our data and these previous findings may result from species-specific differences, purity of OSP, and use of oocytes matured and fertilized in vitro during our study.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…It is a highly glycosylated molecule normally produced by the secretory epithelial cells of the oviduct (1,2). Its synthesis and secretion is regulated during the menstrual cycle with the highest concentrations of oviduct-specific glycoprotein found during the periovulatory period when estrogen levels are high and it is believed to play a role in fertilization and early embryonic development (3)(4)(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…ZP3 is the primary speciesspecific binding site for sperm, and species-specifically induces sperm to undergo the acrosome reaction (21). ZP2 binds acrosome-reacted sperm and has been termed the secondary sperm receptor (22). The role of OGP in fertilization remains unclear, but estrous oviductal fluid, which would contain OGP, plays a role in species-specific gamete interaction (28).…”
mentioning
confidence: 99%